Transparency of clinical trials in pancreatic cancer: An analysis of availability of trial results from the ClinicalTrials.gov database - Huang, Ren-Qian; Zhou, You; Zheng, Hai-Xia; Wang, Dan; Zheng, Xiao-Yi; Li, Zhao-Shen; Hu, Liang-Hao (Frontiers in Oncology, 2023)
Background: Pancreatic cancer (PC) is a highly malignant tumor of the digestive system. As clinical trials involving PC are increasingly being conducted, the transparency of the generated data has become an important issue of concern. In other areas of medicine, clinical trial transparency presents a worrying state of affairs. However, at present, there has been no study examining the transparency of data derived from PC clinical trials. Methods: A comprehensive search was conducted in the ClinicalTrial.gov database for clinical trials investigating pancreatic cancer as of June 2022. We examined the availability of clinical trial results and recorded the characteristics of the trials. Results: A total of 856 trials were included in this study, of which 668 were completed and 188 were terminated or suspended. The results of 626 trials (73.13%) were available, of these 230 trials (26.87%) did not disclose any information on the trial data in any form. The publication rate for trials with available results was 86.10%, but the report rate on ClinicalTrial.gov was only 39.78%. Conclusion: Although approximately 90% of clinical trial investigating interventions on patients with PC have published study results, 30% of trials did not report any findings, and the disclosure of trial results from ClinicalTrial.gov was unsatisfactory. In general, there is still room for improvement in the transparency of PC clinical trials.